2011
DOI: 10.1074/jbc.m110.206680
|View full text |Cite
|
Sign up to set email alerts
|

The Non-canonical Protein Binding Site at the Monomer-Monomer Interface of Yeast Proliferating Cell Nuclear Antigen (PCNA) Regulates the Rev1-PCNA Interaction and Polζ/Rev1-dependent Translesion DNA Synthesis

Abstract: Rev1 and DNA polymerase (Pol) are involved in the tolerance of DNA damage by translesion synthesis (TLS). The proliferating cell nuclear antigen (PCNA), the auxiliary factor of nuclear DNA polymerases, plays an important role in regulating the access of TLS polymerases to the primer terminus. Both Rev1 and Pol lack the conserved hydrophobic motif that is used by many proteins for the interaction with PCNA at its interdomain connector loop. We have previously reported that the interaction of yeast Pol with PCNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
43
1
5

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(49 citation statements)
references
References 51 publications
0
43
1
5
Order By: Relevance
“…However, de Groote et al (44) recently argued against this assertion by showing the BRCT domain, together with a further N-terminal region, to bind to recessed, phosphorylated 5Ј ends of double-stranded DNA. REV1 probably has a PCNA-binding site(s) in its C-terminal region (12,46,47). Furthermore, although Akagi et al (48) have shown that the accumulation of human endogenous REV1 into locally UV-irradiated regions of nucleus depends on the interaction with pol , Andersen et al (45) have reported that the recruitment of the human endogenous REV1 is independent of the interaction with pol .…”
Section: Discussionmentioning
confidence: 99%
“…However, de Groote et al (44) recently argued against this assertion by showing the BRCT domain, together with a further N-terminal region, to bind to recessed, phosphorylated 5Ј ends of double-stranded DNA. REV1 probably has a PCNA-binding site(s) in its C-terminal region (12,46,47). Furthermore, although Akagi et al (48) have shown that the accumulation of human endogenous REV1 into locally UV-irradiated regions of nucleus depends on the interaction with pol , Andersen et al (45) have reported that the recruitment of the human endogenous REV1 is independent of the interaction with pol .…”
Section: Discussionmentioning
confidence: 99%
“…It could be due to different affinities of pol and REV1 for the monoubiquitinated PCNA homotrimer. Yeast REV1 reportedly binds to PCNA on the homotrimer region by its PAD domain (38). If this interaction is also valid in human REV1, a small molecule that binds to the PCNA homotrimer region, such as T2AA, could efficiently inhibit REV1 functions.…”
Section: Discussionmentioning
confidence: 99%
“…Instead, mono-ubiquitination of PCNA likely exerts its TLS-promoting activity through Rev1. Rev1 interacts with PCNA through its BRCT-domain and through the polymerase-associated domain [106,108,109], and shows additional interactions with ubiquitinated PCNA through its UMB motif [107,110]. The affinity of Rev1 for mono-ubiquitinated PCNA is higher than that for unmodified PCNA, further emphasizing the essential role of Rev1 in mutagenesis [107,110,111].…”
Section: Regulation Of Mutagenesismentioning
confidence: 99%